Regulation of conformity qualimetrical excavation zones to regulatory restrictions sale of ore products (Journal of Geography and Environmental Management, 2016)
The article describes a new method of working out their qualitative evaluation of the technology of low-power reservoirs in mining.
Keywords: minerals; stocks wire